(untitled) (Historia, 2021)
1. Hermann Giliomee: Die Kaap tydens die Eerste Britse Bewind 1795-1803 2. Louis Cohen: Reminiscences ofJohannesburg and London 3. H.M. Hole: Old Rhodesian Days 4. A.J. Venter: Coloured - a profile of two million South Africans 5. Anna de Villiers: Barrewets oor Drakensberg 6. Stephan Viljoen: Economic System in World History 7. Gerald Shaw: Some beginnings, The Cape Times, 1876-1910 8. Doreen Lamb: The Republican Residents 9. F.A. van Jaarsveld: Probleme by die Ondemgmn Geskiedenrj 10. L.G. Brandon: History, A Guide to Admnced Study 11. E.G. Davis: The First Sex 12. A.M. Josephy: The Indian Heritage of Americ `13. C.C. Eloff (red.): 00rlo ;dogboekie mn H.S. Oosterhogen 14. M. Schoonraad: Walter Battis